(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2019)
Sulfonamide moieties were added to certain quinoline and pyrimido[4,5-b]quinoline compounds in the hunt for novel cytotoxic agents with better anticancer properties. In vitro anticancer screening was performed on all freshly synthesised target compounds using a human breast cancer cell line (MCF7). In vitro anticancer screening identified the most effective chemicals, which were then tested in conjunction with -radiation for their in vitro anticancer efficacy. It was also discovered that novel chemicals made in the lab docked with the carbonic anhydrase enzyme.